LTE CELL LEVEL LAYER MANAGEMENT AUTO OPTIMIZATION (2016)
Systems and methods are provided to administer a wireless telecommunication network (WTN) having a plurality of cell sites. Network data is received from a data source for a subject cell site. A baseline performance of the subject cell site is determined. Parameters to optimize for the subject cell site based on the baseline performance are identified. Load balancing is performed on the subject cell site by comparing a normalized user equipment (UE) downlink (DL) throughput at a first cellular frequency band to a second cellular frequency band. A cellular coverage of the subject cell site is adjusted based on a voice over LTE (VoLTE) drop call rate for a predetermined time period and a normalized UE DLL throughput. A layer management is performed on the subject cell site.